Optical tools for understanding the complexity of β-cell signalling and insulin release - Frank, James A; Broichhagen, Johannes; Yushchenko, Dmytro A; Trauner, Dirk; Schultz, Carsten; Hodson, David J (Nature reviews. Endocrinology, 2018)
Following stimulation, pancreatic β-cells must orchestrate a plethora of signalling events to ensure the appropriate release of insulin and maintenance of normal glucose homeostasis. Failure at any point in this cascade leads to impaired insulin secretion, elevated blood levels of glucose and eventually type 2 diabetes mellitus. Likewise, β-cell replacement or regeneration strategies for the treatment of both type 1 and type 2 diabetes mellitus might fail if the correct cell signalling phenotype cannot be faithfully recreated. However, current understanding of β-cell function is complicated because of the highly dynamic nature of their intracellular and intercellular signalling as well as insulin release itself. β-Cells must precisely integrate multiple signals stemming from multiple cues, often with differing intensities, frequencies and cellular and subcellular localizations, before converging these signals onto insulin exocytosis. In this respect, optical approaches with high resolution in space and time are extremely useful for properly deciphering the complexity of β-cell signalling. An increased understanding of β-cell signalling might identify new mechanisms underlying insulin release, with relevance for future drug therapy and de novo stem cell engineering of functional islets.
Keywords: homeostáza; Glucose; hodnocení rizik; Genetic Predisposition to Disease; Risk Assessment; signální transdukce; Homeostasis; Diabetes Mellitus, Type 2; glukosa; incidence; Signal Transduction; diabetes mellitus 2. typu; Animals; sekrece inzulinu; lidé; Humans; zvířata; beta-buňky; Sensitivity and Specificity; senzitivita a specificita; Insulin-Secreting Cells; Incidence; Insulin Secretion; genetická predispozice k nemoci